Intra-Arterial Liver-Directed Therapies for Neuroendocrine Hepatic Metastases - Gupta, Sanjay (Seminars in Interventional Radiology, 2013)
Hepatic metastases, which are frequently seen in patients with neuroendocrine tumors (NETs), have a major adverse impact on the patient's quality of life and survival. Surgery is the treatment of choice for hepatic metastases but is possible in only a small percentage of patients. Systemic chemotherapy yields disappointing results. Somatostatin analogs are effective in controlling symptoms in many of these patients; however, the disease can become refractory to treatment. Transcatheter intra-arterial liver-directed therapies, such as hepatic artery embolization, chemoembolization, and radioembolization are frequently used in patients with NETs metastatic to the liver, especially in patients with refractory, unresectable, or recurrent disease. These treatments are effective in palliating the hormonal symptoms as well as achieving objective tumor responses. This review focuses on the technique, safety, and clinical efficacy of hepatic artery embolization, chemoembolization, and radioembolization in patients with metastatic NETs.
Keywords: neuroendocrine; metastases; chemoembolization; radioembolization; interventional radiology